Pengaruh Brand Awareness, Influencer Marketing, dan Online Customer Review Terhadap Keputusan Pembelian (Studi Kasus pada Produk Bittersweet by Najla) - Malya Destari; Andrian Andrian (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to examine the influence of brand awareness, influencer marketing, and online customer reviews on purchasing decisions for Bittersweet by Najla products. The background of this research is based on the rapid development of digital marketing, which has significantly changed consumer behavior in making purchasing decisions. This study employed a quantitative research approach, with data collected through questionnaires distributed to 100 respondents selected using a purposive sampling technique. The data were analyzed using SPSS through validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and the coefficient of determination. The findings indicate that brand awareness and influencer marketing have a positive and significant effect on purchasing decisions. Meanwhile, online customer reviews have a positive influence but do not significantly affect purchasing decisions. Simultaneously, all three variables were found to have a significant effect on purchasing decisions. The results of this study are expected to serve as a reference for companies in developing more effective digital marketing strategies to continuously improve consumers' purchasing decisions.